Socio-ecological barriers to access COVID-19 vaccination among Burmese irregular migrant workers in Thailand - Tual Sawn Khai (Elsevier, 2023)
Thailand is a migration hub in ASEAN (Association of Southeast Asian Nations), with more than 3.9 million migrant workers, accounting for 10% of the country's workforce. The government of Thailand has moved from a pandemic to an endemic state of living with the SAR-CoV2 virus as a new normal since over half of the population has been vaccinated. There is, however, an estimated 1.3 million irregular migrant workers in Thailand who are not covered by Social Security Schemes (SSS) and are likely to have not been vaccinated. This study examines the socio-ecological barriers to accessing vaccination among Burmese irregular migrant workers in Thailand. Qualitative and quantitative data were collected from NGO (Non-Government Organizations) workers and Burmese irregular migrants through an online survey and in-depth interviews. The study reported that over 90% of Burmese irregular migrants were unvaccinated. The main reasons for the low vaccination rate include exclusion from the vaccine distribution program, high cost of the vaccine, perceived low quality of vaccine, language barriers, lack of vaccine information, private and public discrimination against migrants, fear of being detained and deported, and difficulties in finding time and transportation to go to vaccination centres. The Thai government should employ culturally competent interpreters to disseminate vaccine information and potential side effects to encourage vaccinations in order to prevent further casualties and curb the global health crisis. Moreover, it is imperative that the Thai government provide free vaccines to all immigrants regardless of their status and amnesty from deportation and detention during the vaccination period.